Differential Effects of Acute Treatment With Antipsychotic Drugs on Peripheral Catecholamines - Boyda, Heidi N.; Ho, Amanzo A.; Tse, Lurdes; Procyshyn, Ric M.; Yuen, Jessica W. Y.; Kim, David D.; Honer, William G.; Barr, Alasdair M. (Frontiers in Psychiatry, 2020)
Antipsychotic drugs represent the most effective treatment for chronic psychotic disorders. The newer second generation drugs offer the advantage of fewer neurological side-effects compared to prior drugs, but many cause serious metabolic side-effects. The underlying physiology of these side-effects is not well understood, but evidence exists to indicate that the sympathetic nervous system may play an important role. In order to examine this possibility further, we treated separate groups of adult female rats acutely with either the first generation antipsychotic drug haloperidol (0.1 or 1 mg/kg) or the second generation drugs risperidone (0.25 or 2.5 mg/kg), clozapine (2 or 20 mg/kg), olanzapine (3 or 15 mg/kg) or vehicle by intraperitoneal injection. Blood samples were collected prior to drug and then 30, 60, 120 and 180 minutes after treatment. Plasma samples were assayed by HPLC-ED for levels of norepinephrine, epinephrine and dopamine. Results confirmed that all antipsychotics increased peripheral catecholamines, although this was drug and dose dependent. For norepinephrine, haloperidol caused the smallest maximum increase (+158%], followed by risperidone (+793%), olanzapine (+952%) and clozapine (+1684%). A similar pattern was observed for increases in epinephrine levels by haloperidol (+143%], olanzapine (+529%), risperidone (+617%) then clozapine (+806%). Dopamine levels increased moderately with olanzapine [+174%], risperidone [+271%] and clozapine [+430%]. Interestingly, levels of the catecholamines did not correlate strongly with each other prior to treatment at baseline, but were increasingly correlated after treatment as time proceeded. The results demonstrate antipsychotics can potently regulate peripheral catecholamines, in a manner consistent with their metabolic liability.